WATER IN THE KINGDOM OF SAUDI ARABIA: SUSTAINABLE MANAGEMENT OPTIONS - Khodran. H. Al-Zahrani; M. B. Baig (Journal of Animal and Plant Sciences, 2011)
Water is one of the most precious and valuable resources affecting the Saudi development plans. The acute shortage of fresh water resources poses a major challenge in Saudi Arabia. Demand for fresh water is on the rise as sufficient water is no longer available to meet daily needs. Some 95% of water comes from aquifers. Desalination plants and waste water reclamation projects provide about 4% and 1% water respectively. About 30% of the water for household consumption comes from desalinating plants. The users of desalinated water of the Kingdom represent about 26% of world total. In the light of the present scenario of declining water resources and increasing demand, the Kingdom must consider the most viable option i.e. Water Demand Management (WDM). However, other necessary water conservation measures should not be overlooked. The article also suggests that in order to use water resources efficiently, factors such as economics, social aspects and environmental conditions must receive due consideration.
Keywords: Precious and Scarce; Water Demand Management; Conservation Measures; Water Price; Extension